Intercultural Verbal and Nonverbal Communication Between Lembak and Javanese Communities in Rejang Lebong, Bengkulu - Robby Aditya Putra; Exsan Adde; Pajrun Kamil; Anrial Anrial; Ainul Mamnuah (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
This study aims to understand how the Lembak and Javanese communities interact amid significant language differences. The research was conducted in Rejang Lebong Regency, Bengkulu, focusing on both verbal and nonverbal interactions in daily life. Language and cultural value differences often pose challenges in intercultural communication. Using a descriptive qualitative approach, data were collected through participatory observation and in-depth interviews with members of both ethnic groups. Data analysis was conducted interactively, including data reduction, data presentation, and drawing conclusions. The findings reveal notable differences in verbal language use, specifically lexical ambiguities and